The Ariege ‘Refuge’: Advantage and Diversity of a Host Topography - William Berthomière; Christophe Imbert (Revue de Géographie Alpine)
Alexander von Humboldt wrote that ‘the arrangement of mountains… divide the surface of the earth into basins or vast cirques…and influence the range of cultures, habits, institutional forms and national hates’ (Debarbieux, 2012, p.13). While this formulation may seem outdated, von Humboldt’s reflection remarkably still resonates more than a century and a half later with recent events in mountainous areas affected by European migration policies and border control. Drawing on the life histories of refugee activists in the French department of Ariège, we reveal a complex territoriality that, depending on the spaces considered, produces singular and distinct forms of mobilisation, inherited from past migratory experiences, the engagement of neo-rurals and the social networks linking mountains, valleys, piedmont towns and the Toulouse conurbation. We highlight the uniqueness of the Ariège ‘refuge’, where mechanisms of migration control are relativised through a distancing enabled by both the topography and the social space of exile activism.